NEO PEREMPUAN: Kajian Atas Pemikiran Qasim Amin - Samsul Huda (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2020)
This article highlights Qasim Amin thoughts (1863-1908). She is one the prominent figures pioneering the idea of emancipation in Islamic contemporary era. Employing historical and hermeneutic approaches, this article is to reactualize her thoughts on Womens’ Moslem in Egypt in their same crucial aspects like education, hoouseholds, hijab (cover), poligamy and talak (divorce). Her thoughts reflect and indicate her sense of crisis as well as her intellectual response. She is not an utopist, but to reposition the women into their dignity in the light of Islamic point of views.